The Hotel Management Students’ Needs on English Online Learning at Politeknik Internasional Bali - Luh Sri Damayanti (ITScience (Information Technology and Science), 2022)
During pandemic Covid-19 which was started at the beginning of 2020, the learning process in all levels of education in Indonesia has been shifting to online learning. Politeknik Internasional Bali as one of the vocational higher education institutions has also implemented online learning for all the subjects. English is one of them. Since then, the needs of students in learning are also changed depending on the learning situation. This research was quantitative research aiming at finding out and examining the hotel management students' needs for English online learning at Politeknik Internasional Bali. There were 20 students involved as participants in the research. The researcher used questionnaires to collect the data. The data gained were analyzed using descriptive statistics to find out the percentage of the needs. Based on the analysis, it was found that the students needed online learning that meet these criteria. The hotel management students need online learning that is (1) fun, (2) contains various activities, (3) provides clear instructions, (4) provides team works, (5) provides learning modules, (6) easily accessed, (7) providing interactive learning, and (8) containing various features. The results of this research can be a source for the development of online learning media, in the forms of modules, learning activities, and others that can meet and are suitable for students' needs.